The Impact of Telemedicine on Cancer Care Advancement in Accessibility, Treatment Delivery, and Patient Outcomes - Khan , Sidra Khalid; Syed Misbah Ul Haq; Khan, Asaad Khalid; Khan, Saad Khalid; Abbas , Faizan; Abbas, Syedda Zainab (Indus Journal of Bioscience Research, 2025)
This research examines the effect of telemedicine on cancer care, including treatment delivery, team coordination, and patient outcomes like quality of life. The research used a descriptive analysis design with a sample size of 25 cancer patients and 55 healthcare providers from Punjab, Pakistan. Data were collected through surveys and institutional records on key indicators such as team coordination, treatment adherence, and quality of life scores. The Chi-Square test was used to analyze the difference in team coordination from face-to-face to virtual settings, while ANCOVA was used to analyze the effect of telemedicine on quality of life after adjusting for age and socioeconomic status. The findings showed a significant difference in team coordination (p < 0.05), where all patients shifted to remote care after introducing telemedicine. Further, the ANCOVA analysis also showed a statistically significant improvement in quality of life among telemedicine-users (p = 0.03), indicating that telemedicine has positive effects on patient outcomes over traditional face-to-face care. These findings suggest that telemedicine is a very effective intervention in delivering cancer care, with both patient satisfaction and coordination of care being ensured. Additional research, however, is needed to explore its long-term effect and the potential effect of other factors like digital literacy and age on its effectiveness. Telemedicine significantly enhances cancer care by improving access, coordination, and patient quality of life. It fosters real-time collaboration, reduces travel burdens, and boosts treatment satisfaction. ANCOVA results show better outcomes with telemedicine. Future research should explore long-term impacts and demographic influences to ensure equitable and effective implementation across diverse populations.